2013
DOI: 10.1186/1749-8090-8-75
|View full text |Cite
|
Sign up to set email alerts
|

Less invasive coronary artery revascularization with a minimized extracorporeal circulation system: preliminary results of a comparative study with off-pump-procedures

Abstract: BackgroundCoronary-artery-bypass-grafting (CABG) with conventional extracorporeal circulation (CECC) is associated with adverse effects such as systemic inflammatory response leading to a decrease in systemic vascular resistance and hemodynamic instability. Modern "less invasive" procedures have been established recently which potentially avoid negative side effects of CECC. The aim of this study was to compare perioperative outcome following coronary revascularization using either a minimized extracorporeal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Despite all these potential beneficial effects for the mini-bypass systems, some other studies showed that there is no difference in post-operative outcomes [2,10,[18][19][20][21][22][23][24]. These discrepancies in clinical outcomes between different studies suggest that patients enrolled in those studies may represent a heterogenous group of patients who may benefit especially high-risk patients and those who may not benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all these potential beneficial effects for the mini-bypass systems, some other studies showed that there is no difference in post-operative outcomes [2,10,[18][19][20][21][22][23][24]. These discrepancies in clinical outcomes between different studies suggest that patients enrolled in those studies may represent a heterogenous group of patients who may benefit especially high-risk patients and those who may not benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all these potential bene cial effects for the mini-bypass systems, some other studies showed that there is no difference in post-operative outcomes [2,10,[18][19][20][21][22][23][24]. These discrepancies in clinical outcomes between different studies suggest that patients enrolled in those studies may represent a heterogenous group of patients who may bene t especially high-risk patients and those who may not bene t.…”
Section: Introductionmentioning
confidence: 99%
“…The minimal extracorporeal circulatory system consists of a centrifugal pump, a membrane oxygenator, a short heparin-coated line, and a vacuum line that can be added if necessary [14, 15]. The venous reservoir and the standard vacuum line in the conventional cardiopulmonary bypass system are not present in this circuit.…”
Section: Introductionmentioning
confidence: 99%